Upaya Meningkatkan Asertivitas Melalui Layanan Bimbingan Kelompok pada Siswa Asuh Kelas IX SMP Negeri 1 Sakra Barat - Dahman Dahman (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2019)
This study aims to determine whether group guidance services can improve the assertiveness of class IX students of SMPN 1 Sakra. The sampling technique used in this study was random sampling, by randomly taking 20 students. Methods of collecting data using a psychological scale. Validity test: Product Moment correlation formula and reliability: Alpha formula. Sample homogeneity: Chi quadratic formula. Data analysis: Wilcoxon test. Based on the results of the pre test average student assertiveness in the experimental group 57% (low) and the control group 61% (moderate). Whereas in the post test results in the experimental group after being given group guidance services, the average student assertiveness became 75% (high) and the post test results of the average assertiveness of the control group students who were not given group guidance services became 62% (moderate). Wilcoxon test results obtained Thitung = 6 and Ttabel = 8. If Thitung <Ttabel then Ho is rejected and Ha is accepted. Because Thitung <Ttabel then there is a significant difference between the value of the post test of the two sample groups, it means that group guidance services can improve student assertiveness.